Resilience of Atlantic Slippersnail Crepidula fornicata Larvae in the Face of Severe Coastal Acidification - Kriefall, Nicola G.; Pechenik, Jan A.; Pires, Anthony; Davies, Sarah W. (Frontiers in Marine Science, 2018)
Globally, average oceanic pH is dropping, and it will continue to decline into the foreseeable future. This ocean acidification (OA) will exacerbate the natural fluctuations in pH that nearshore ecosystems currently experience daily, potentially pushing marine organisms to their physiological limits. Adults of Crepidula fornicata (the Atlantic slippersnail) have proven remarkably resilient to many environmental changes, which is perhaps not surprising considering that they are common intertidally, have a geographically large native range, and have been extremely successful at invading coastal waters in many other parts of the world. However, the larvae of C. fornicata have been shown to be somewhat more vulnerable than adults to the effects of reduced pH. Research to date has focused on the physiological impacts of OA on C. fornicata larvae; few studies have explored shifts in gene expression resulting from changes in pH. In the present study, we examined the response of young (4-day old) C. fornicata larvae to two extreme OA treatments (pH 7.5 and 7.6) relative to pH 8.0, documenting both phenotypic and genome-wide gene expression responses. We found that rearing larvae at reduced pH had subtle influences on gene expression, predominantly involving downregulation of genes related to growth and metabolism, accompanied by significantly reduced shell growth rates only for larvae reared at pH 7.5. Additionally, 10-day old larvae that had been reared at the two lower pH levels were far less likely to metamorphose within 6 h when exposed to inducer. However, all larvae eventually reached similarly high levels of metamorphosis 24 h after settlement induction. Finally, there were no observed impacts of OA on larval mortality. Taken together, our results indicate that far future OA levels have observable, but not severe, impacts on C. fornicata larvae, which is consistent with the resilience of this invasive snail across rapidly changing nearshore ecosystems. We propose that future work should delve further into the physiological and transcriptomic responses of all life history stages to gain a more comprehensive understanding of how OA impacts the littoral gastropod C. fornicata.